Caracterización del producto del proceso de viscoreducción, para la conversión de aceite vegetal, aceite de alga y búnker - Davis Barquero, Alexander (2013)
Through the use of a high pressure and high temperature reactor conditions a visbreaking is simulated, with the purpose of producing green fuels, replacing a fraction fuel oil #6 with vegetable oils. A 25% (m/m) of palm (Elaeis guineensis), castor (Ricinus communis), jatropha (Jatropha curcas) and 10% algae (Undaria pinatifida) oils, 450 ° C and 5 min of reaction time were utilize and the products were compared with the standards used by RECOPE. The replacement of 25% m/m by vegetable oil, increases by 6,1% the fraction of total diesel oil, improves the cetane index, decreases viscosity the amount of aromatic material and the amount of sulphur respect to 100% bunker The use of fluidized bed reactors or hydrogen mix for increase the saturated products are recommended for future research.